The causal relationship between diet habits and cholelithiasis: a comprehensive Mendelian randomization (MR) study - Xie, Lin; Xu, Mingzhi; Lei, Yahan; Li, Juan; Xie, Jiajia (Frontiers in Nutrition, 2024)
Epidemiological studies show dietary habits can have an impact on the risk of cholelithiasis, but the relationship is still unclear. We used a comprehensive Mendelian randomization (MR) study to explore the relationship between dietary habits and cholelithiasis.The 18 dietary habits were divided into six categories: meat foods, cereals, vegetables, fruits, dairy products, beverages, and condiments. Cholelithiasis data came from a GWAS meta-analysis and the FinnGen consortium. The inverse variance weighted (IVW), the weighted median (WM), and MR-Egger approaches were used as the main MR analysis methods. In addition, multiple sensitivity analysis and Meta-analysis were performed to verify the robustness of the results.Dried fruit intake (odds ratio (OR) = 0.568; 95% confidence intervals (CI), 0.405-0.797; p = 0.001) was discovered to reduce the risk of cholelithiasis. The sensitivity analysis and metaanalysis showed reliable results for the relationship between dried fruit intake and cholelithiasis.Our study found that dried fruit intake is a protective factor in the development of cholelithiasis. However, the mechanisms of action need to be further explored.